Context-based chemistry teaching within the 4Ex2 model: Its ımpacts on metacognition, multiple ıntelligence, and achievement - Koçak Altundağ, Canan (Journal of Turkish Science Education, 2018)
The purpose of this study is to investigate the impact of context-based chemistry education on the metacognition and multiple-intelligences of preservice chemistry teachers, and their achievement in chemistry lessons in the laboratory environment that includes the 4Ex2 model. Within the framework of the general chemistry laboratory lesson, the treatment group was taught with a context-based chemistry teaching method in the chemistry laboratory using the 4Ex2 model, while the traditional methods were applied in the control group’s lessons. It is determined that after the application, abilities to control the metacognitive thoughts of the preservice teachers, who were taught with a context-based chemistry teaching method in the chemistry laboratory within the 4Ex2 model, positively changed compared to those included in the control group. Additionally, the results showed that the preservice teachers in the treatment group, who received context-based chemistry teaching within the 4Ex2 model, were more successful; therefore, this model is an effective teaching method.